Key Determinants of SMEs Sustainable Performance in West Sumatra: A PLS-SEM Analysis - Hary Fandeli; Micko Tomas; Fitrah Qalbina; Nasywa Firdaus Har (Jurnal Optimasi Sistem Industri, 2026)
Rising environmental pressures from population growth and industrial expansion in Indonesia necessitate sustainable business practices. Yet, adoption among Small and Medium-sized Enterprises (SMEs) remains obstructed by low energy efficiency, inadequate waste management, limited technological and financial access, and managerial shortcomings. Using‍‌‍‍‌‍‌‍‍‌ two theories, resource based view (RBV) and institutional theory (IT), this study has mapped the relationships between internal and external factors and the triple-bottom-line performance of SMEs. This study investigates and tests these relationships amongst the factors that influence environmental, social, and economic sustainability performance by Partial Least Squares Structural Equation Modeling (PLS-SEM). This study designs the approach as a cross-sectional survey, gathering primary data from 110 SMEs to assess the proposed relationships among internal, external, and sustainability performance. Internal factors consist of green entrepreneurial orientation (GEO), green innovation (GI), and leadership commitment (LC), while market orientation (MO) and stakeholder pressure (SP) represent the external factors. Findings indicate that market orientation (MO) has a positive and significant effect across the entire triple-bottom-line (financial, social, environmental), whereas stakeholders pressure (SP) exerts a significant positive effect only on the financial and social dimensions. On the other hand, the internal factor comprising green entrepreneurial orientation (GEO), green innovation (GI), and leadership commitment (LC) does not significantly impact sustainability performance. These results indicate that among the external drivers examined, market orientation is the most comprehensive predictor of sustainability performance, whereas stakeholder pressure has a significant effect only on the financial and social dimensions. Practically, Indonesian SMEs are advised to constantly interpret and react to market signals and stakeholder expectations, whereas, policymakers are recommended to pair the tool of stakeholder pressure with capability-enhancement programs in terms of the operational system.